Intragastric Botulinum Toxin Injection and Botulism: An Alarm for Clinicians - Mojtaba Mojtahedzadeh; Farhad Najmeddin; Elham Pourheidar; Atabak Najafi; Reza Bahman; Ehsan Yousefi-Mazhin; Hossein Karballaei-Mirzahosseini; Rezvan Hassanpour (Case Reports in Critical Care)
Clostridium botulinum produces the most potent bacterial toxin, botulinum toxin A (BTXA), which has various therapeutic and cosmetic indications. Intragastric BTXA injection is a new obesity treatment method that was argued to be safe due to the inactivation of BTXA through the liver or metabolization within the gastric wall. However, a 36-year-old woman was admitted to the intensive care unit (ICU) due to developing botulism as a result of an intragastric injection of BTXA. The diplopia, headaches, ptosis, decreased muscle force, and respiratory distress two days after injection were her first chief complaints, and also, she experienced significant dysphagia, hoarse voice, thick tongue, constipation, hyposmia, and hypogeusia after two weeks. This case report highlights the necessity for physicians to have sufficient information about this method and consider possible life-threatening adverse effects including botulism.